Kanban and process mining in the task management - Mendes, Vitor; Ribeiro Junior, Elio; Garcia, Cleiton; Malucelli, Andreia (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2018)
In a world continuously changing with markets that are in permanent evolution and in contend, the companys must inovate, be more flexible, offer quality and respond swiftly. These factors do not apply for product manufacture processes only, but for software development processes aswell. This paper describes an account of experiences with the use of Kanban to improve the activities management in an ERP's development. To do this, a mapping of the current process was carried out, so to propose a set of improvements in the management of activities. As a result, a set of tools were implemented to enable a clear view and control over the activities, as well as to integrate the Issue Tracking System with the Kanban board. Furthermore, a process mining technique was used to estimate the time of conclusion of the activities and to detect performance problem.